THE MOST EFFECTIVE ENGLISH GRAMMAR SYLLABUS FOR FRESHMEN DUE TO CURRICULUM ADJUSTMENT - Imelda Bella Megadihas (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
Freshmen of English Department have various backgrounds which affecttheir understanding on English grammar. Meanwhile, English Grammar is the basic need for English Department freshmen to deal with other subjects in the following semesters. Therefore, teaching grammar to first semester studentsneedsstrategies in order to achieve the goal of existing curriculum. One of the strategies is setting the best syllabus on the related course.English Letters Department of University of Sanata Dharma, recently, adjustedits curriculum in 2016. It compounds the syllabus of Structure course of freshman in batch 2016 becomes doubled from the syllabus applied before batch 2016. In other words, grammar study learnt by freshmen of batch before 2016 in the first and second semester advanced into compactly learnt in only one semester by the freshmen of batch 2016. With the same referencewhich isUnderstanding and Using English Grammar 3rd edition by Betty S. Azar used by the two categories of subjects in this research, later, will be discovered that the syllabus with fewer materials is the most effective syllabus.